On isomorphic representations of generalized definite automata - Gécseg, Ferenc; Imreh, Balázs (Acta Cybernetica, 2001)
In this paper, the generalized definite automata are studied. In particular, systems which are isomorphically complete for this class with respect to the αi-products are characterized.